A modified IRS-III chemotherapy regimen leads to prolonged survival in children with embryonal tumor with multilayer rosettes. Issue 1 (18th September 2020) - Hanson, Derek; Hoffman, Lindsey M; Nagabushan, Sumanth; Goumnerova, Liliana C; Rathmann, Allison; Vogel, Timothy; Ziegler, David S; Chi, Susan
Abstract: Background: Embryonal tumor with multilayer rosettes (ETMR) is a rare CNS malignancy affecting young children that carries a very poor prognosis. Treatment with intensive surgical resection, radiotherapy, and high-dose chemotherapy is insufficient treatment in the vast majority of cases. Effective, biologically based therapies for this tumor are therefore desperately needed. The Dana-Farber Cancer Institute–modified IRS-III protocol incorporates preclinically active agents, such as doxorubicin and actinomycin D, into the treatment regimen for ETMR and may improve patient outcomes. Methods: The authors present a case series of 5 children with ETMR treated with an IRS-III-based chemotherapy backbone. Results: All 5 patients received a gross-total tumor resection. Patients received between 12 and 51 weeks of IRS-III therapy at the discretion of their treating physician. Four patients received focal radiation therapy, with the fifth patient instead receiving a cycle of high-dose chemotherapy with autologous stem cell rescue. Four patients have progression-free survival of more than 18 months. Chemotherapy treatment was reasonably tolerated by all 5 patients with one case of mild sinusoidal obstructive syndrome and one case of Grade 3 peripheral neuropathy. Conclusions: The patient outcomes in this small cohort are far better than would be expected based on the historical survival for this tumor. Given the tremendous need for effective therapy for ETMR, further investigation of this approach is warranted. An international consensus protocol based on the IRS-III regimen has been developed and will be available through a multicenter clinical trial and a global treatment registry.